1998
DOI: 10.1074/jbc.273.8.4705
|View full text |Cite
|
Sign up to set email alerts
|

S100A1 Regulates Neurite Organization, Tubulin Levels, and Proliferation in PC12 Cells

Abstract: As a first step in determining what cellular processes are regulated by the calcium-modulated protein S100A1 isoform in neurons, the effects of ablated S100A1 expression on neurite organization and microtubule/tubulin levels in PC12 cells were examined. A mammalian expression vector containing the rat S100A1 cDNA in the antisense orientation with respect to a cytomegalovirus promoter was constructed and transfected into PC12 cells. Indirect immunofluorescence microscopy confirmed decreased S100A1 protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…For example, in nonmuscle cells it has been reported that PEL98 (S100A4), binds to the nonmuscle tropomyosin isoform 2, regulates tropomyosin-actin interactions and suppresses the metastatic potential of Lewis lung carcinoma cells [Takenaga et al, 1994]. In a similar manner, S100A1 expression in PC12 cells has been demonstrated by antisense inhibition experiments to be important in regulating tubulin levels, neurite organization and proliferate capacity [Zimmer et al, 1998]. S100A1 and S100A4 normally co-localize to actin stress fibers within the cell [Mandinova et al, 1998].…”
Section: Calcyclin As a Regulator Of Actin Binding Protein-protein Inmentioning
confidence: 92%
“…For example, in nonmuscle cells it has been reported that PEL98 (S100A4), binds to the nonmuscle tropomyosin isoform 2, regulates tropomyosin-actin interactions and suppresses the metastatic potential of Lewis lung carcinoma cells [Takenaga et al, 1994]. In a similar manner, S100A1 expression in PC12 cells has been demonstrated by antisense inhibition experiments to be important in regulating tubulin levels, neurite organization and proliferate capacity [Zimmer et al, 1998]. S100A1 and S100A4 normally co-localize to actin stress fibers within the cell [Mandinova et al, 1998].…”
Section: Calcyclin As a Regulator Of Actin Binding Protein-protein Inmentioning
confidence: 92%
“…Inhibition of expression of S100A1 in PC12 cells also results in a decrease in cell proliferation rate (Zimmer et al, 1998), a finding that was interpreted as suggestive of a role of this protein in the modulation of the activity of an unknown transcription factor. S100A2 is markedly down-regulated in breast tumor biopsies and can be re-expressed in mammary carcinoma cells by azadeoxycytidine treatment (Lee et al, 1992).…”
Section: Inhibition Of Protein Phosphorylationmentioning
confidence: 96%
“…To prove that, we used the PC12 model cell line, which is frequently used in the studies of S100A1 activity (23). We have studied the effects of S-nitrosylation on Ca 2ϩ binding and on the high resolution three-dimensional structure of human apo-S100A1, 4 aiming at the elucidation of yet unknown factors regulating various biological functions of the protein.…”
Section: S100a1 Is a Member Of The Camentioning
confidence: 99%
“…They are known to express S100A1 at a high level (23). PC12 cells not stimulated with nitric oxide donors or other compounds were used to determine whether endogenous S-nitrosylation of S100A1 protein might be observed in a cellular system.…”
Section: S100a1 Protein Is Endogenously S-nitrosylated In Pc12mentioning
confidence: 99%